Respuestas

2012-06-29T02:06:48+02:00

fàcil  :
            2
          x    +    5x   +   6   = 0    ,  si usamos la forma normal no te sale tenes k usar la                                                          formula general :                                         
                                -b  +-   V (b)2 -  4 (a)(c)
                                              2(a) 
                                             
       -(5) +- V  (5)2  -  4 (1)(6)
                    2 (1) 
                                                                       
      -5 +- V  25- 24           =                   -5 +-V1         =  -5 +-  1             
            2                                                 2                     2

     x1= (-5 + 1)/  2= -2            x2= (-5-1)/2=  -3                   Salñudos !